Conceptual fundamentals of ecological tourism development in Ukraine - Y. O. Kiselyov; M. I. Adamenko; R. M. Rudy (Kazimierz Wielki University, 2020)
The article covers elaborating the conceptual framework of the development of ecological tourism. The work expounds the notion and principles of ecotourism adopted in accordance with international agreements, and evolves the criteria of an ecotourism offer. The proposed wording of the modern concept of ecotourism implies ecological educating the participants of ecotourism activities and local residents and is aimed at attaining the socio-economic objectives on condition that the natural and cultural heritage is preserved for future generations. The national experience and the features of developing ecotourism in Belarus are analyzed, including the analysis of ecotourism in protected areas, agritourism, and greenways. The most significant socio-economic aspects of the growth of ecological tourism are produced.